An empirical test of 'universal' biomass scaling relationships in kelps: evidence of convergence with seed plants. Issue 3 (1st August 2016) - Starko, Samuel; Martone, Patrick T.
Summary: Biomass allocation patterns have received substantial consideration, leading to the recognition of several 'universal' interspecific trends. Despite efforts to understand biomass partitioning among embryophytes, few studies have examined macroalgae that evolved independently, yet function ecologically in much the same ways as plants. Kelps allocate photosynthate among three organs (the blade(s), stipe(s) and holdfast) that are superficially convergent with organs of land plants, providing a unique opportunity to test the limits of 'universal' trends. In this study, we used an allometric approach to quantify interspecific biomass partitioning patterns in kelps and assess whether embryophyte‐based predictions of biomass scaling can be applied to marine macrophytes that lack root‐to‐leaf hydraulic transport. Photosynthetic area and dry mass were found to scale to approximately the ¾ power and kelp biomass allocation patterns were shown to match closely to empirical measures of allometric scaling among woody plants. Larger kelp species were found to have increased relative stipe and holdfast mass than smaller species, highlighting important consequences of size for marine macroalgae. Our study provides insights into the evolution of size in the largest marine macrophytes and corroborates previous work suggesting that the morphology of divergent lineages of photoautotrophs may reflect similar selective pressures.